2014
DOI: 10.1182/blood-2014-02-554279
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic graft-versus-host disease with bortezomib

Abstract: • Bortezomib ameliorates sclerodermatous cGVHD responses by inhibiting germinal center B cells while maintaining GVT effects in murine models.• Bortezomib provides therapeutic benefits for patients with active steroidrefractory cGVHD.Chronic graft-versus-host disease (cGVHD) following allogeneic hematopoietic stem cell transplantation (HSCT) has emerged as a predominant complication following HSCT and has a distinct etiology. We and others have previously demonstrated that bortezomib, a proteasome inhibitor, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 33 publications
1
51
0
2
Order By: Relevance
“…At the most final stage of aberrant B-cell response, depletion of alloantibodyproducing plasma cells by proteosome inhibition (eg, bortezomib) is supported by evidence of efficacy in animal systems and early clinical studies. 160 Finally, targeting macrophages by preventing differentiation and survival in tissue through the inhibition of CSF-1R has proven highly effective in animal systems, 112 as has the inhibition of TGFb. 112,161 18.…”
Section: 29mentioning
confidence: 99%
“…At the most final stage of aberrant B-cell response, depletion of alloantibodyproducing plasma cells by proteosome inhibition (eg, bortezomib) is supported by evidence of efficacy in animal systems and early clinical studies. 160 Finally, targeting macrophages by preventing differentiation and survival in tissue through the inhibition of CSF-1R has proven highly effective in animal systems, 112 as has the inhibition of TGFb. 112,161 18.…”
Section: 29mentioning
confidence: 99%
“…21,24 GC reactions may play a major role in the pathogenesis of cGVHD in mice. [25][26][27] GC-derived "plasmablast-like" B cells are increased in human cGVHD. 11 Recent studies have shown that the latter cell subset bears regulatory properties and may be the main IL-10-producing B-cell subset in mice.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study investigating the use of bortezomib as salvage therapy for steroid-refractory/dependent cGVHD was recently conducted based on favorable results from mice experiments [97]. Ten patients were enrolled in the doseescalating study, which started from 0.2 mg/m 2 subcutaneously once a week, and then increased every 2 weeks by 0.2 mg/m 2 until the patients responded or grade III to IV dose-limited toxicity occurred.…”
Section: Salvage Treatment For Steroid-refractory/dependent Cgvhdmentioning
confidence: 99%